Dynamic analysis on noise and vibration study of flexible wiper blade system - Salim, Mohd. Azli (Trans Tech Publications Ltd., 2010)
Chatter is one of the unwanted noise and vibration phenomenon which are generated during the wiper operation. It is a low frequency and self-excited vibration that is often generated before and after the wiper reverses its direction. This leads to a poor visibility and annoying sound to the driver and passengers. Therefore, this paper is aimed to propose a technique that can be apply to tackle this problem. Hence, an existing two-dimensional mathematical model of a wiper system available in the open literature is adopted. Firstly, the baseline model is simulated in order to observe its vibration response. Then, an input shaping control scheme is introduced into the baseline model. It is found that the input shaping control scheme can reduce the vibration level approximately by 30 percents from the baseline model.